تأثير محو الأميات الكتابية بطريقة الملاحظة نحو ترقية مهارة الكتابة في الصف الأول بمدرسة المتوسطة الإسلامية المتفوقة الكهف تارك سدووارجو - Hanifah, Umi; Barid, Bintan Nuruzzakiyah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2019)
Language learning in most schools is still conventional, especially during kitabah learning. Teacher only uses the tarjamah method and provides objective training to students, so that student’s understanding is still abstract and passive in kitabah learning. Therefore, researchers apply writing literacy with an observation method that aims to improve student’s writing skills. The type of research that uses in this study is quantitative research with experimental classes to determine the causes and consequences of the application of writing literacy with the observation method. The research subjects were class VII the number of students there were 40 students and the research instruments used are: 1) Observations, 2) interviews, 3) documentation, and 4) tests. The results of this study indicate that the influence of writing literacy application with the observation method in improving student’s writing skills.